2021
DOI: 10.3389/fonc.2021.647066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Methylated CLIP4 in Stool for Early Detection of Colorectal Cancer: A Training Study in Chinese Population

Abstract: BackgroundEarly detection of colorectal cancer (CRC) and precancerous lesion is vitally important for mitigating CRC morbidity and mortality. Aberrant DNA methylations in certain promoter regions have been identified to be closely associated with CRC development and progression, suggesting their potential as diagnostic biomarkers for early detection. In this study, we evaluated the performance of methylated CLIP4 in stool specimens as a potential biomarker for CRC detection.MethodsA total of 321 subjects out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that methylated CAP-Gly domain containing linker protein family member 4—CLIP4, may be a potential biomarker for early detection of CRC. An mCLIP4 assay was carried out on stool and tissue samples, showing a sensitivity of 90.3% and specificity of 88.4% ( Figure 4 ) [ 72 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that methylated CAP-Gly domain containing linker protein family member 4—CLIP4, may be a potential biomarker for early detection of CRC. An mCLIP4 assay was carried out on stool and tissue samples, showing a sensitivity of 90.3% and specificity of 88.4% ( Figure 4 ) [ 72 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“… Sensitivities of stool mCLIP4 test in detecting different CRC stages (after Cao et al, 2021) [ 72 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous non-invasive methods based on liquid biopsy biomarkers have been developed, most of these methods only targeted one cancer type [ 32 , 33 ]. As we all know, the cost of the current liquid biopsy method is still significantly higher than that of traditional serum tumor markers [ 34 ]; thus, it is difficult to apply those new methods in clinical practice in developing countries such as China. In this study, we detected three UGC types together for the first time and reacted the markers simultaneously in a single tube.…”
Section: Discussionmentioning
confidence: 99%
“…With systematic bioinformatics screening and clinical verification, our study showed that a combination of serum CK20 and hyper-methylated CLIP4 was a novel and effective biomarker for CRC diagnosis with 91.67% sensitivity and 82.54% specificity in the training cohort; and 95% sensitivity and 81.7% specificity in the validation cohort. It was more sensitive than CLIP4 hyper-methylated alone in stool specimens (90.3% sensitive, 88.4% specificity) [ 33 ]. Comparing with previous serum CRC biomarkers, CK20/hyper-methylated CLIP4 was more effective than CEA/MMP-7/TIMP-1 (sensitivity: 70.3%, specificity: 91.3%) [ 34 ], RUNX3/SFRP1/CEA (sensitivity 84.71%) [ 35 ], LRG1/EGFR/ITIH4/ HPX/SOD3 (sensitivity: over 70%, specificity: 89%) [ 36 ], anti-SLP2/-p53/-SEC61B/-PLSCR1 (sensitivity: 64.1%, specificity: 80%) [ 37 ], miR-203a-3p/miR-145-5p/miR-375-3p/miR-200c-3p (sensitivity: 81.52%, specificity: 73.33%) [ 38 ], miR-144-3p/miR-425-5p/miR-1260b (sensitivity: 93.8%, specificity: 91.3%) [ 39 ], and less than CCL20/IL-17A (sensitivity: 96.1%, specificity: 96.5%) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%